Impact of intellectual capital on financial vulnerability of pharmaceuticals sector in Pakistan - Shoaib Aslam; Shahid Amin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Generally, Intellectual capital (IC) is recognized as a strategic asset of a company and used for value creation to sustain the competitive advantage. Value can be created by intangibles that are not always depicted in annual reports but are helpful to face financial shocks. The purpose of this study is to identify the impact of IC on financial vulnerability (FV) of pharmaceutical sector in Pakistan. Quantitative data collected from the annual reports of listed pharmaceutical sector in Pakistan to test the study empirically. Data is examined by using PLS-Graph version 3. IC efficiency is measured through value added intellectual coefficient (VAIC) model developed by Pulic (2000, 2004). FV is measured by using the vulnerability model introduced by Tuckman and Chang (1991). Results show consistency with expectations moreover, IC efficiency of pharmaceutical firms has significant impact on FV. This study extends the literature of FV with the combination of IC.
Keywords: 330; intellectual capital; financial vulnerability; structural equation modeling; partial least square; pharmaceutical sector